2021
DOI: 10.1002/1348-9585.12232
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of socioeconomic status and treatment interruption among Japanese workers during the COVID-19 pandemic

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In addition to direct effects of severe pneumonia and acute respiratory failure, COVID-19 has also had indirect health effects. COVID-19-related treatment interruption, particularly in patients with chronic diseases, is an emerging issue in several countries (5,6), including Japan (7). Studies have reported a significant decrease in the number of prescriptions during the pandemic compared to before, and that 40 % of patients requiring regular visits have been seen less frequently (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to direct effects of severe pneumonia and acute respiratory failure, COVID-19 has also had indirect health effects. COVID-19-related treatment interruption, particularly in patients with chronic diseases, is an emerging issue in several countries (5,6), including Japan (7). Studies have reported a significant decrease in the number of prescriptions during the pandemic compared to before, and that 40 % of patients requiring regular visits have been seen less frequently (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…These factors presumably have differing degrees of impact depending on the level of infection in the region, such as incidence rate and cumulative COVID-19 cases. In addition, patients with unstable socioeconomic status are more likely to discontinue treatment (7,14,15). Areas with higher prevalence of COVID-19 may be more affected by the loss of job security and other factors that affect individuals with unstable socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] In addition, across the world interruptions to medical treatments have been caused by the COVID-19, including in Japan. [14] Interruptions and delays in treatment may exacerbate pre-existing health conditions and increase complications, which may further increase the incidence of sickness presenteeism. In parallel, the COVID-19 pandemic has led to precarious employment conditions in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…It has caused interruptions in treatment and increased anxiety due to infection among workers with chronic illnesses. [14][15][16] Lockdown and social distancing have resulted in public health challenges such as loneliness and stress. [17,18] These challenges lead to worker presenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…19 Lockdowns and social distance mandates have additionally brought about challenges such as loneliness and stress. 20 , 21 These events have further increased presenteeism among workers, especially those in precarious socioeconomic situations, who are more likely to experience presenteeism. 22 , 23 , 24 Workers with presenteeism may be at high risk of poverty, as they are more likely to experience a decline in income due to reduced working hours, changes to less demanding tasks, and transitions to more precarious forms of employment.…”
Section: Introductionmentioning
confidence: 99%